Husband–Wife Relations from the Salaf Perspective and the Challenges of Modernity: a Comparative Analysis - Muhsan Syarafuddin; Muhammad Nurul Fahmi; Farchan Mu'aziz; Ratno Pambudi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
This study aims to analyze husband-wife relations from the salaf perspective and examine the challenges of modernity toward contemporary Muslim family relations. The research employs a qualitative method with a normative-comparative approach through library research. Primary sources include the Qur’an, hadith, classical tafsir, and fiqh literature, while secondary sources consist of scholarly journals and contemporary studies on modern Muslim families. The findings reveal that the salaf perspective views marital relations as a spiritual and moral bond founded upon the principles of mu‘āsyarah bil ma‘rūf, qiwāmah, compassion, and complementary role distribution. Meanwhile, modernity has significantly transformed family relations through the rise of individualism, gender equality, dual-income families, and digital culture, leading marital relations to become more flexible and negotiative. The comparative analysis demonstrates that modernity potentially reduces several foundational principles of marital relations in the salaf perspective, particularly regarding responsibility, role structure, and family orientation based on trust and moral commitment. This study highlights the importance of formulating Muslim family relations that integrate Islamic normative values with contemporary social dynamics in a proportional and adaptive manner.